Strengthening the Golden Visa Indonesia: Best Practices from Several Countries - Firdaus Silabi Al-Attar; Maria Puspitasari; Renny Nurhasana (Green Publisher Indonesia, 2025)
Golden Visa is an investment-based immigration policy scheme that grants long-term residence permits for foreign nationals. Since 2023, Indonesia has officially adopted this model through regulations aimed at attracting foreign investors, global talents, world leaders, and the diaspora. This article aims to evaluate the initial implementation of the Indonesian Golden Visa, compare it with similar practices in other countries such as Portugal, the United Arab Emirates, Singapore, and Malaysia, and formulate policy strengthening recommendations. With a qualitative approach based on literature studies and regulatory analysis, this paper finds that the success of Golden Visa is highly dependent on the selectivity of applicants, the quality of investment contributions, and cross-sectoral governance capacity. In Indonesia, although until April 2025 the investment realization value from Golden Visa has reached Rp35.4 trillion, challenges such as transparency, policy integration, and supervision of investment realization are still the main obstacles. Lessons from other countries show the importance of policy designs that are not only administratively appealing but also impact long-term economic transformation. Therefore, Indonesia needs to formulate a Golden Visa model that is not only oriented towards the amount of investment but also accompanied by an impact-based selection mechanism, periodic evaluation of contributions, and integration of cross-sectoral policies such as immigration, taxation, and investment. This scheme also needs to be directed at strategic sectors such as technology, renewable energy, and education, in order to create long-term added value and support the national development agenda in an inclusive and sustainable manner.